Object Affordances Potentiate Responses but Do Not Guide Attentional Prioritization - Yamani, Yusuke; Ariga, Atsunori; Yamada, Yuki (Frontiers in Integrative Neuroscience, 2016)
Handled objects automatically activate afforded responses. The current experiment examined whether objects that afford a response are also prioritized for attentional processing in visual search. Targets were pictures of coffee cups with handles oriented either to the right or the left. Subjects searched for a target, a right-handled vs. left-handled coffee cup, among a varying number of distractor cups oriented in the opposite direction. Responses were faster when the direction of target handle and the key press were spatially matched than mismatched (stimulus-response compatibility effect), but object affordance did not moderate slopes of the search functions, indicating the absence of attentional prioritization effect. These findings imply that handled objects prime afforded responses without influencing attentional prioritization.